Co-Housing as a Strategy to Combat Relational Poverty of Older People - Letizia Carrera (Richtmann Publishing, 2022)
The pandemic experience from Covid-19 has heightened the awareness of the impact that relational poverty has on the quality of life, especially of older people’s lives. The obligation to stay inside their homes to protect them from the risk of infection has had the indirect effect of precipitating many elderly people into a state of solitude from which, at least in part, the city had been protecting them until then. The pandemic has shown how older citizens live the shortage of relationships and the solitude of housing as factors that can heavily affect the quality of their lives. But this difficult historical moment has been an opportunity to implement a series of projects dedicated to over 65 people so that they could be guaranteed a fullness of possibilities. Within them there is “CondiViviamo” activated in Bari (Italy) and focused on the possibility of realizing an experience of cohousing as an instrument to contrast the economic uneasiness and, above all, the relational poverty. The starting assumption is both to guarantee older people a better existential condition, and to make them protagonists of this process. The project, carried out in a multifactorial perspective, is initially aimed at a limited number of elderly subjects, but it has the secondary purpose of defining a model exportable to other cities in the same territory of Apulian region and even at national level. The analysis of the outcomes of the project will also be functional to the definition of future operational guidelines for public social policies. Received: 22 August 2022 / Accepted: 20 October 2022 / Published: 5 November 2022